Inukshuk on the grounds of the Scott Polar Research Institute, University of Cambridge, England ... - Campbell, Sandy (University of Alberta Library, 2014)
This inukshuk stands beside the Scott Polar Research Institute side entrance at Madingly Road, Cambridge, UK. It originated in Kinngait (Cape Dorset), Qikiqtaaluk (Baffin Island), Nunavut in 1964 and it was commissioned by Charles Gimpel, who donated it to the Museum. It comprises approximately 16 main pieces and several smaller irregular pieces of pink, black and white granite secured with concrete filler. SPRI ref Y: 2005/8. Information courtesy Health Lane, Librarian and Keeper of the Collections at Scott Polar Research Institute, University of Cambridge. ...